Organização política e sindical de assistentes sociais do Tribunal de Justiça de São Paulo: uma perspectiva de classe em debate - Macedo, Eliane Gomes de (2018)
This research focus on the political and labor union organization of social workers of the São Paulo State Court of Justice (Tribunal de Justiça de São Paulo, TJSP) from the perspective of their class membership. To this purpose, it firstly recovers the path of social worker’s political organization in Brazil, in particular the worker’s class mobilization from the 1970s on with the new unionism; secondly, it historically reconstructs the process of political and labor union organization of the TJSP social workers; and finally, the constitution of workers associations and labor unions and the specificities of the political and labor union organization of the social workers is put into question in relation to the impacts caused by the State formal workers union structure and the peculiarities of the so-called “middle class labor unionism”. The lack of research on this topic, specially on unionism in the public service, which is the main playing field for social workers, justify the relevance of the proposed investigation in such an institution as the São Paulo State Judiciary, characterized by a large associative tradition and a multiplicity of workers unions and professional category associations that, on the one hand, represent the manifold universe of their own professionals while, on the other hand, reveal a deep political fragmentation that hinders collective organization and unity around a common agenda. Guided by the above depicted topics, bibliographic and documentary research was undertaken from different sources. In order to collect empirical data, a qualitative research with semi-structured interviews and surveys with social workers and other professionals were executed. The aim was to investigate the constitutive dimensions of their organization by giving voice to relevant actors intentionally chosen among the direction of labor unions and associations, as well as grassroots leadership, emphasizing the participation of social workers in several spheres of organization and struggle in TJSP. The sample consisted of fifteen subjects and the data were complemented with systematic observation and field journal. The analysis suggests that the strategies of organization concerning the entry in the State labor union’s structure, which were legitimated through the workers’ struggle for full union freedom, have generated new modes of leadership and grassroots fragmentation, reinforcing a historical trend of the category that can only be tackled by a broader articulation with other working class struggle instruments, such as political parties and social movements